Transcultural approach to the health-related quality of life of cancer patients - Namie Okino Sawada; Bianca Sakamoto Ribeiro Paiva; Carlos Eduardo Paiva; Helena Megumi Sonobe; María Paz García-Caro; Francisco Cruz-Quintana (Rev Rene)
Objective: to compare the health-related quality of life of cancer patients under chemotherapy treatment in Brazil and Spain. Methods: a cross-sectional study, whose data collection took place at the Hospital de Câncer and Hospital Universitário, with socio-demographic characterization instruments and European Organization for Research and Treatment of Cancer. Results: female, white, marital status, grade school students, catholic religion and the unskilled profession predominated in both countries. The scores of health-related quality of life in the health global status and the functions of role performance and cognitive functions were higher in the Brazilian sample, whereas fatigue, pain, dyspnea, insomnia and diarrhea symptoms were more present in the Spanish population, with statistically significant differences. Conclusion: health-related quality of life was better among Brazilians.